PENGEMBANGAN PEMBELAJARAN AKUNTANSI MELALUI MEDIA KOMIK DI SMK KATOLIK SANTA MARIA PONTIANAK - Antonius Antonius; Mashudi Mashudi; Endang Purwaningsih (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2019)
This research is a type of research and development in learning Accounting in High School. The development model applied consists of; 1) the need analysis phase, 2) the product design stage, 3) the production stage, 4) the validation and evaluation stages, 5) the revision stage, 6) the product testing phase, and 7) the analysis phase and the final revision. The validation phase is carried out by product validation carried out by accounting material experts, learning media experts and accounting learning practitioners, namely the Santa Maria Catholic Vocational High School accounting teacher Pontianak. The product developed was tested on 34 grade XI Santa Maria Catholic Vocational High School Pontianak. Data collection is done by questionnaire and test. Questionnaire for eligibility for experts and practitioners, opinion questionnaires and test questions addressed to students. The results of the study show that the learning media in the form of Accounting Comics is very feasible to use. In testing the learning field using accounting comics, it was successful in increasing the average student test scores. Thus, the comic-shaped learning media is very feasible to use for learning accounting at the Catholic Santa Maria Vocational High School Pontianak.